Effects of surface and twinning energies on twining-superlattice formation in group III–V semiconductor nanowires: a first-principles study. (21st March 2019) - Akiyama, Toru; Nakamura, Kohji; Ito, Tomonori
Abstract: The formation of twin plane superlattices in group III–V semiconductor nanowires (NWs) is analyzed by considering two dimensional nucleation using surface and twinning energies, obtained by performing electronic structure calculations within density functional theory. The calculations for GaP, GaAs, InP, and InAs demonstrate that surface energies strongly depend on the growth conditions such as temperature and pressure during the epitaxial growth. Furthermore, the calculated twinning energies are found to be much smaller than previously estimated values by the dissociation width of edge dislocations, which lead to smaller segment lengths. We also find that the nonlinear relationship between segment length and NW diameter depending on constituent elements is due to the difference in twinning energies. These results imply that twinning formation as well as surface stability are crucial for the formation of twin plane superlattices in group III–V semiconductor NWs.